2013
DOI: 10.1002/clen.201200508
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of 11 Sulfonamides by HPLC–UV and Application for Fast Screening of Their Aerobic Elimination and Biodegradation in a Simple Test

Abstract: Sulfonamides (SAs) are one of the most frequently used antibiotics. SAs have been found in various environmental compartments. If SAs are not degraded in the environment, they can affect bacteria by their antibiotic properties and contribute to bacterial antibiotic resistance. Therefore, the biodegradability of 11 SAs (sulfanilamide, sulfaguanidine monohydrate, sulfadiazine, sulfathiazole, sulfapyridine, sulfamerazine, sulfamethoxypyridazine, sulfachloropyridazine, sulfamethazine, sulfamethoxazole, and sulfadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Impacts of Cl À on the photodegradation As Cl À is one of the important constituents and exhibits gradient variation in estuarine waters, we explored its effects on the photodegradation of the SAs with different concentrations relevant to estuarine conditions. In the dark controls, no obvious loss of the SAs was observed, implying that the decay from other processes than photodegradation such as sorption or biodegradation/hydrolysis was negligible, which is consistent with previous studies that SAs are resistant to biodegradation (Mahmoud et al, 2013) and hydrolysis (Białk-Bieli nska et al, 2012). Linear regression of ln (C t /C 0 ) vs time (t) showed that the photodegradation of the SAs followed a pseudo-first order kinetics (r > 0.98, p < 0.05).…”
Section: Resultssupporting
confidence: 91%
“…Impacts of Cl À on the photodegradation As Cl À is one of the important constituents and exhibits gradient variation in estuarine waters, we explored its effects on the photodegradation of the SAs with different concentrations relevant to estuarine conditions. In the dark controls, no obvious loss of the SAs was observed, implying that the decay from other processes than photodegradation such as sorption or biodegradation/hydrolysis was negligible, which is consistent with previous studies that SAs are resistant to biodegradation (Mahmoud et al, 2013) and hydrolysis (Białk-Bieli nska et al, 2012). Linear regression of ln (C t /C 0 ) vs time (t) showed that the photodegradation of the SAs followed a pseudo-first order kinetics (r > 0.98, p < 0.05).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the adverse drug reaction (ADR) of FQNs had obtained more attention. Traditionally, drug residues analysis relied on chromatography, such as high-performance liquid chromatography (HPLC), 2 liquid chromatography/mass spectrometry (LC-MS), 3 and LC-MS/MS. 4 However, chromatography has many limitations such as time-consuming and instruments valuableness.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 SMX is also widely used in farming and aquaculture. [3][4][5][6] Due to the characteristics of SMX, approximately 15-25% is incompletely metabolized and excreted into the surrounding environment from the human or animal body aer ingestion. [7][8][9][10] The wide use of SMX raises particular concerns for human health because its presence in the environment may harm human health and lead to antibiotic resistance, [11][12][13] as well as being a serious threat to soil and water ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In China, SMX is released from four major sources: industry, hospitals, farms, and households; some SMX is released into water and soil without pre-treatment. 6,14 The degradation of SMX in soil, therefore, has become a major environmental concern. To date, different physicochemical techniques have been tested to remove SMX from polluted soil or water including oxidation, [15][16][17] adsorption, 18-21 photodegradation 22 and hydrolysis.…”
Section: Introductionmentioning
confidence: 99%